Severe injection site reactions after subcutaneous administration of Sayana®: a retrospective, post-marketing analysis of WHO and Swiss spontaneous pharmacovigilance reports - Annika Jödicke; Hendrike Dahmke; Beat Damke; Martina Schäublin; Gerd A. Kullak-Ublick; Stefan Weiler (Swiss Medical Weekly, 2017)
PURPOSE